(untitled) (Sociologisk Forskning, 2020)
The aim of the article is to explore trade unions’ use of Internet and social media in communicating with members and to understand membership in the digital era. A point of departure is that new forms of relationships between individuals and organizations are on the rise as our present societies become more digitalized, which has changed how citizens interact, mobilize, and organize. Digitalization has been discussed as a driving factor behind membership decline and disengagement, but also as an opportunity to revitalize the labor movement. Drawing on theories on social movements, interest groups, and civil society organizations the article adopts a multi-dimensional perspective that understands membership as participation, resource, representativeness, and identity. It presents results from a qualitative study of two Swedish trade unions. The empirical data consists of documentation from websites and social media complemented by interviews with employees with knowledge about the unions’ Internet and social media communication. The results show that Swedish unions do not seem to be adapting to new technologies, rather using them as opportunities for strengthening and reviving membership without re-formulating its premises.